Innovative Fluorescent Polymers in Niosomal Carriers: A Novel Approach to Enhancing Cancer Therapy and Imaging - GÖKALSIN, BARIŞ (My University, 2024)
Cancer is anticipated to become the pioneer reason of disease-related deaths worldwide in the next two decades, underscoring the urgent need for personalized and adaptive treatment strategies. These strategies are crucial due to the high variability in drug efficacy and the tendency of cancer cells to develop resistance. This study investigates the potential of theranostic nanotechnology using three innovative fluorescent polymers (FP-1, FP-2, and FP-3) encapsulated in niosomal carriers, combining therapy (chemotherapy and radiotherapy) with fluorescence imaging. These cargoes are assessed for their cytotoxic effects across three cancer cell lines (A549, MCF-7, and HOb), with further analysis to determine their capacity to augment the effects of radiotherapy using a Linear Accelerator (LINAC) at specific doses. Fluorescence microscopy is utilized to verify their uptake and localization in cancerous versus healthy cell lines. The results confirmed that these niosomal cargoes not only improved the antiproliferative effects of radiotherapy but also demonstrate the practical application of fluorescent polymers in in vitro imaging. This dual function underscores the importance of dose optimization to maximize therapeutic benefits while minimizing adverse effects, thereby enhancing the overall efficacy of cancer treatments.
Keywords: Biyomedikal Mühendisliği; Yaşam Bilimleri; Biyoteknoloji; Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Biomedical Engineering; Life Sciences; Biotechnology; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik Bilişim Ve Teknoloji (Eng); Temel Bilimler (Sci); Yaşam Bilimleri (Life); Mühendislik; Malzeme Bilimi; Mikrobiyoloji; Mühendislik Biyomedikal; Malzeme Bilimi Biyomateryal; Malzeme Bilimi Çokdisiplinli; Polimer Bilimi; Biyoteknoloji Ve Uygulamalı Mikrobiyoloji; Engineering Computing & Technology (Eng); Natural Sciences (Sci); Life Sciences (Life); Engineering; Materials Science; Microbiology; Engineering Biomedical; Materials Science Biomaterials; Materials Science Multidisciplinary; Polymer Science; Biotechnology & Applied Microbiology; Biyomühendislik; Fizik Bilimleri; Biyomalzemeler; Polimerler ve Plastikler; Malzeme Kimyası; Bioengineering; Physical Sciences; Biomaterials; Polymers and Plastics; Materials Chemistry; fluorescent polymers; niosomes; radiotherapy; theranostic treatment